Mathematical Literacy as a Key Competency for Maritime Education: Systematic Review of Cadet Competencies - Novitasari, Novitasari; Agustina, Eka Nurmala Sari; Fachrudin, Achmad Dhany; Irfan, Saiful (Universitas Islam Lamongan, 2024)
This study discusses the role of mathematical literacy as the main competency that cadets need to have in the field of maritime education. Through a systematic literature review (SLR), the mathematical literacy competencies needed by cadets in the maritime field are navigation, problem solving, use of modern technology, operational management, critical and logical thinking, and accurate data-based decision making. This systematic review provides an illustration of literacy mastery Mathematics not only supports cadets' understanding of basic maritime concepts, but also improves cadets' abilities in dealing with challenges or unexpected situations on board ships and while at anchor. Therefore, developing mathematical literacy must be a priority in cadet education and training programs to produce graduates who are competent and ready to face the complexity of the global maritime industry.